Komparasi Penerapan Model Pembelajaran Berbasis Proyek dengan Model Pembelajaran Inkuiri Terbimbing Terhadap Pemahaman IPA (Natural Sains) Siswa di SDN Pembina Tolitoli - Idris, Nuramaliah; BK, Muh. Khaerul Ummah; Marto, Hasia (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study aims to compare the implementation of project-based learning models with guided inquiry learning models in improving students' understanding of science materials at SDN Pembina Tolitoli. The type of research used in this study is quantitative using the true experiment method of pretest-posttest type with a comparative study conducted on students of SDN Pembina Tolitoli with a total population of 633 students. The research sample consisted of three classes, namely class VI A with 28 students, class VI B with 30 students, and class VI C with 26 students selected using probability sampling. Data collection was carried out through observation and testing, and data analysis using SPSS 25 software. The results showed that the significance value of the project-based learning model (PJBL) was 0.737 <0.05 and the guided inquiry model was 0.906 <0.05. Thus, it can be concluded that the implementation of the project-based learning model (PJBL) and the implementation of the guided inquiry model have been effectively given to classes VB and VC, the results of Indonesian language lessons of students of SDN Pembina Tolitoli and there are differences between classes that implement the project-based learning model (PJBL) and the implementation of the guided inquiry model where the results in the class implementing the project-based learning model (PJBL) are 88.86 while the implementation of the Guided Inquiry model is 88.92.